Math You Can Really Use--Every Day - Alan David (Wiley, 2007)
Math You Can Really Use--Every Day skips mind-numbing theory and tiresome drills and gets right down to basic math that helps you do real-world stuff like figuring how much to tip, getting the best deals shopping, computing your gas mileage, and more. This is not your typical, dry math textbook. With a comfortable, easygoing approach, it: